Damage Detection and Performance Evaluation of Photovoltaic Panels Used in Rural Area through Thermography Analysis - Sedigheh Sorkhani; Masoud Iranmanesh; Naeimeh Gholamrezaei (Biomechanism and Bioenergy Research, 2022)
In recent years, due to environmental issues, the installation of distributed production sources such as solar sources in electrical energy production systems has been expanding. It is very important to know the state of health of installed photovoltaic panels and their depreciation rate to maximize the amount of output energy of these panels.  In this research, some common types of panel defects were investigated experimentally by thermal imager. The parameters affecting the thermal images were investigated by taking images of two similar panels, one a sound panel and a damaged panel and the performance parameters of the panels were measured by a solar analyzer. Based on the results obtained by using thermal images and image processing in MATLAB software, it was identified the defect location of the panel in a short time. According to the investigations, the histogram diagram of the healthy panel corresponds to the normal distribution, while the histogram diagram of the defective panel does not correspond to the normal distribution diagram and has an elongation to the left. Checking the voltage and power parameters of the panels shows that in the defective panels, the voltage has dropped by 1.2 V and the power has dropped by 26.8 W.